LANDSLIDE SUSCEPTIBILITY MAPPING BY GIS-BASED QUALITATIVE WEIGHTING PROCEDURE IN CORINTH AREA - Foumelis, M.; Lekkas, E.; Parcharidis, I. (Bulletin of the Geological Society of Greece, 2018)
Landslide susceptibility mapping refers to a division of the land into zones of varying degree of stability based on an estimated significance of causative factors in inducing the instability. Maps of landslide susceptibility (relative hazard) are usually prepared on regional scales from 1:25.000 - 1:50.000. An advantage of regional studies is that they allow rapid assessment and hence larger areas can be covered in short durations. Factors (data layers) used for the preparation of the landslide susceptibility map were obtained from different sources such as topographic maps, geological maps and satellite images. All the above data layers were converted to raster format in the GIS, each representing an independent variable of a constructed spatial database. Computerization of the database would be necessary to make such analysis possible within an acceptable time frame. According to their relative importance to slope instability in the study area, the various classes of different data layers were assigned weights between 0,0 and 1,0 (collectively adding to 1,0). The overall susceptibility was calculated as an index named SPI (Susceptibility Potential Index), expressing the combination of the different weighted layers into a single map using a certain combination rule. Reclassification of susceptibility scores, based on natural breaks in the cumulative frequency histogram of SPI values, were used to delineate various susceptibility zones namely, very high, high, moderate, low and very low. Verification of results by overlaying susceptibility map and landslide inventory data and adjustment of zone's boundaries was the last stage of the study, allowing the reconsideration in some cases of the weights given